A fluorescence‐based hydrolytic enzyme activity assay for quantifying toxic effects of Roundup® to Daphnia magna. (16th June 2015) - Ørsted, Michael; Roslev, Peter
Abstract: Daphnia magna is a widely used model organism for aquatic toxicity testing. In the present study, the authors investigated the hydrolytic enzyme activity of D. magna after exposure to toxicant stress. In vivo enzyme activity was quantified using 15 fluorogenic enzyme probes based on 4‐methylumbelliferyl or 7‐amino‐4‐methylcoumarin. Probing D. magna enzyme activity was evaluated using short‐term exposure (24–48 h) to the reference chemical K2 Cr2 O7 or the herbicide formulation Roundup®. Toxicant‐induced changes in hydrolytic enzyme activity were compared with changes in mobility (International Organization for Standardization standard 6341). The results showed that hydrolytic enzyme activity was quantifiable as a combination of whole body fluorescence of D. magna and the fluorescence of the surrounding water. Exposure of D. magna to lethal and sublethal concentrations of Roundup resulted in loss of whole body enzyme activity and release of cell constituents, including enzymes and DNA. Roundup caused comparable inhibition of mobility and alkaline phosphatase activity with median effective concentration values at 20 °C of 8.7 mg active ingredient (a.i.)/L to 11.7 mg a.i./L. Inhibition of alkaline phosphatase activity by Roundup was lowest at 14 °C and greater at 20 °C and 26 °C. The results suggest that the fluorescence‐based hydrolytic enzyme activity assay (FLEA assay) can be used as an index of D. magna stress. Combining enzyme activity with fluorescence measurements may be applied as a simple and quantitative supplement for toxicity testing with D. magna . Environ Toxicol Chem 2015;34:1841–1850. © 2015 SETAC